A proposed methodology for the calculation of direct consumption of fossil fuels and electricity for livestock breeding, and its application to Cyprus - Florides, Georgios A.; Kythreotou, Nicoletta; Tassou, Savvas A. (My University, 2012)
On-farm energy consumption is becoming increasingly important in the context of rising energy costs and concerns over greenhouse gas emissions. For farmers throughout the world, energy inputs represent a major and rapidly increasing cost. In many countries such as Cyprus, however, there is lack of systematic research on energy use in agriculture, which hinders benchmarking end evaluation of approaches and investment decisions for energy improvement. This study established a methodology for the estimation of the direct consumption of fossil fuels and electricity for livestock breeding, excluding transport, for locations where full data sets are not available. This methodology was then used to estimate fossil fuel and electricity consumption for livestock breeding in Cyprus. For 2008, this energy was found to be equivalent to 40.3 GWh that corresponds to 8% of the energy used in agriculture. Differences between the energy consumption per animal in Cyprus and other countries was found to be mainly due to differences in climatic conditions and technologies used in the farms
Keywords: Cyprus; Agriculture; Animals; Energy consumption; Fossil fuels